2004
DOI: 10.1089/089277904773582921
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kinetic Vaporization of the Prostate: Clinical Evaluation of a New Technique

Abstract: The IPSS with QOL scores, prostate volumes, and residual urine volumes showed significant decreases and Qmax values showed a significant increase after bipolar plasma kinetic electrovaporization. This treatment modality causes a temporary increase in the PSA concentration, as do other interventional treatment methods, but the measurements on the 30th and 90th days were below preoperative values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 23 publications
9
31
0
2
Order By: Relevance
“…Also in our trial, the B-TUVP had lesser mean hemoglobin drop than B-TURP (0.53 vs. 1.39g/dL) due to superior hemostasis and coagulation (12,34). The published experiences reported the mean postoperative hospitalization and catheterization periods of 1.4-2.08 and 2.2-3.54 days for bipolar vaporization (12,20,44,45). No significant differences were seen in catheterization and hospitalization duration between bipolar electrovaporization (1193 minutes, 1.45 days) and TURP (1007 minutes, 1.5 days) in Dunsmuir and co-workers trial (16 (17)).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Also in our trial, the B-TUVP had lesser mean hemoglobin drop than B-TURP (0.53 vs. 1.39g/dL) due to superior hemostasis and coagulation (12,34). The published experiences reported the mean postoperative hospitalization and catheterization periods of 1.4-2.08 and 2.2-3.54 days for bipolar vaporization (12,20,44,45). No significant differences were seen in catheterization and hospitalization duration between bipolar electrovaporization (1193 minutes, 1.45 days) and TURP (1007 minutes, 1.5 days) in Dunsmuir and co-workers trial (16 (17)).…”
Section: Discussionmentioning
confidence: 50%
“…The operating time had the means of 61 and 63 minutes for B-TUVP and the median of 55 minutes for bipolar plasmakinetic electrovaporization in the published experiences (12,20,45). In Dunsmuir and co-workers trial, the bipolar electrovaporization and TURP had similar operation time (33 vs. 26 minutes, P = 0.78) (16).…”
Section: Discussionmentioning
confidence: 99%
“…16 Subsequently, several studies revealed a lower intra-and perioperative morbidity and functional short-term results comparable to conventional TURP. [17][18][19][20] However, midterm results have been reported to be inferior compared to TURP. 7,21 In 2008, a novel bipolar device using an ergonomic, hemispherical electrode and a different energy setting was launched.…”
Section: Discussionmentioning
confidence: 99%
“…By 2007, the median number of years of experience in urology was 10 years (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Patients in both study arms were treated by the same surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The positive and negative poles are on the same axis and are isolated from each other by a ceramic connecting piece. 7 The Plasmakinetic Generator (Gyrus Medical) generates strong, pulsatile, bipolar energy, which generates the working temperature on the cutting tool, permitting maximum tissue dissection with minimum collateral damage. In addition to allowing effective cutting, it has been constructed to achieve optimum hemostasis and prevent adherence to the tissue.…”
Section: Introductionmentioning
confidence: 99%